Ivan Illich Chebanenko (On the eighty five-year-old Jubilee) (Геологічний журнал, 2010)
An outstanding Ukrainian scientist, geologist and tectonist, Doctor of Sciences in Geology and Mineralogy (1975), Professor (1979), Corresponding Member of the National Academy of Sciences (NAS) of Ukraine (1979), Full Member of the National Academy of Sciences of Ukraine (1982), Honored Scientist (1991), Deputy Director of the Institute of Geological Sciences of the Ukrainian Academy of Sciences (1972—1973, 1975—1978), Head of the Department of Geotectonics at the Institute of Geological Sciences (1978-present), State Prize of Ukraine in the field of science and technology (1992) Ivan I. Chebanenko celebrated his 85th anniversary.